MOOC: ¿Revolución Educativa o Determinismo Tecnológico/Social Sin Cambio? (2013)
Education has changed little in the last century . This is explained in the continued proliferation of literature that asks , hopes or dreams of new and improved forms of education. But we are still with the old idea of the classroom, where a teacher teaches and some students assimilate and follow directions . This regardless of the amount of technology introduced in the educational process . The courses MOOC (Massive Open Online Course) have emerged in recent times as an aspiration to overcome old problems of education and thus get a more comprehensive education , universal, democratic and free. This informative article and research format, check MOOC taught several courses in 2013. The study concludes that educational practice MOOC courses show that there is a strong technological determinism and social determinism that still leaves the old education and educational formats even without specifying new patterns of education.